Aroma Components Analysis and Origin Differentiation of Black Tea Based on ATD-GC-MS and E-Nose - Jianfeng Huang; Tingyu Yan; Jiangfan Yang; Hui Xu (Horticulturae, 2023)
Black tea (Fuyun 6) samples collected from three regions, Youxi, Fu’an, and Datian, were analysed by automatic thermal desorption-gas chromatography–mass spectrometry (ATD-GC–MS) combined with the electronic nose (E-nose) technique to investigate the aroma composition differences between black teas from different regions. The response surface methodology was used to optimize the ATD conditions for extracting the aroma components from the black tea. The results revealed that the optimal conditions for aroma component accumulation from black tea samples included a sample weight of 2.8 g, an adsorption time of 39 min, an adsorption temperature of 75 °C, and a cold trap temperature of −30 °C. The ATD-GC–MS analyses identified a total of 71 aroma components in the black tea samples, of which 31 were utilized to differentiate the origins of the black teas. Additional aroma activity analyses indicated that benzyl alcohol, linalool, hexanal, octanal, and nonanal had odour activity values (OAVs) greater than 10. Additionally, the OAV of decanal exceeded 100, indicating its significant contribution to the aroma profile of Fuyun 6 black tea. The E-nose results demonstrated the ability to differentiate the black tea samples from the three different origins. This study successfully identified the specific aroma substances associated with different tea origins, providing valuable insights into the aroma characteristics of black teas from various regions.